A critical occupational perspective on user engagement of older adults in an assisted living facility in technology research over three years. Issue 3 (2nd July 2020) - Holthe, Torhild; Halvorsrud, Liv; Lund, Anne
ABSTRACT: Digital assistive technology has potential for supporting older adults who depend upon community healthcare services. To boost the efficiency of those services, technological devices are often installed for care recipients as part of governed practice. However, the varying adoption of technology risks widening the digital divide. In response, the Assisted Living project engaged older adults in co-creating knowledge about users' needs, to guide the development of technological solutions designed to support everyday living. This study sought to investigate how eight older adults in an assisted living facility in Norway, aged 81–92 years, evaluated user inclusion in a 3-year technology-oriented research project. Individual interviews, dialogue cafés, interventions with environmental sensors, and a final focus group discussion constituted sites for co-creation of knowledge. Participants' answers to standardised questionnaires and statements during dialogue café meetings were collated into tables and the focus group discussion was thematically analyzed, with three themes identified: motivation for project engagement, experiencing and understanding participation in the project, and mixed feelings towards environmental sensors at home. The project revealed that older adults with impairments could nevertheless meaningfully contribute opinions about their needs. Applying a critical occupational perspective raised awareness regarding sociocultural assumptions about older adults in assisted living as frail and unable to participate, which may reinforce ageist and ableist stereotypes, as well as promote occupational injustice.